Forma, funzione e azione collettiva: Marx e il problema Proudhon - Ricciardi, Maurizio (Bollettino Filosofico, 2025)
The essay examines the relationship between Marx and Proudhon, highlighting the profound theoretical and political differences between them. It focuses on Marx’s distance from Proudhon’s concept of a self-organizing society governed by natural laws, which is underpinned by a functionalist and fundamentally theological vision. In particular, it analyzes the complex Marxian semantics of the Träger, illustrating how individuals are reduced to functions subordinated to the abstract and impersonal domination of capital. The essay then explores its connection to the concept of form, which Marx subjects to constant historical critique to demonstrate its contingency. This critique leads to an important partial result in Marx’s analysis of the Paris Commune as a political form that challenges the functionalism of capital and Proudhonian individualism. Keywords: Association, Cooperation, Ideological Effect, Political Form, Träger